Sternoclavicular Joint Instability and Reconstruction. Issue 16 (15th August 2022) - Provencher, Matthew T.; Bernholt, David L.; Peebles, Liam A.; Millett, Peter J.
Abstract : Chronic instability or degenerative arthritis of the sternoclavicular (SC) joint may occur after traumatic or spontaneous dislocation of the SC joint. Most commonly, chronic instability of the SC joint occurs anteriorly; however, posterior instability has an increased risk of serious complications because of proximity to mediastinal structures. Although chronic anterior instability of the SC joint does not resolve with nonsurgical treatment, patients often have mild symptoms that do not impair activities of daily living; however, chronic anterior SC joint instability may be functionally limiting in more active individuals. In these cases, surgical treatment with either (1) SC joint reconstruction or (2) medial clavicle resection, or both, can be done. Recurrent posterior instability of the SC joint also requires surgical treatment due to risk of injury to mediastinal structures. Recent literature describes various reconstruction techniques which generally show improved patient-reported outcomes and low complication rates.